Residue and bioefficacy of propiconazole against stripe rust on wheat(Triticum aestivum) in Haryana region - SINGH, RAJENDER; CHAUHAN, REENA; AHLAWAT, SUSHIL; CHOPRA, INDU; RANA, M K (The Indian Journal of Agricultural Sciences, 2025)
The experiment was conducted during 2019 to 2021 at Chaudhary Charan Singh Haryana Agricultural University, Hisar, Haryana to evaluate the effectiveness of six different fungicides against stripe rust on wheat (Triticum aestivum L.) crop. Propiconazole is recommended for spray against stripe rust, therefore, its residues were analyzed at six different growth stages (Tillering; Stem elongation; Booting; Awn emergence, i.e. 50% ear head emergence; Flowering (complete anthesis) and Milk development stage in wheat and straw using GC-MSMS after its application. The experiment was laid out in a randomized block design (RBD) in triplicate plot size of 2.5 m × 2 m. Studies showed that, propiconazole 25% ec (Tilt) was found to be economically best for controlling stripe rust as well as enhancing the grain yield among tested chemicals. The residuals were less than the quantitation limit (0.01 mg/kg) at tillering, stem elongation and booting stage. However, residues were above maximum residual limit (0.05 mg/kg) as well as quantitation limit in grains at awn, milk development and dough stage. Thus, from the current study it can be concluded that use of propiconazole is safe only when good agricultural practice is adopted and sprayed before ear head emergence stage.